Home, refuse, and reuse during the Early Helladic III to the Middle Helladic I transitional period: A social zooarchaeological study of the Asine bothroi - Macheridis, Stella (Opuscula. Annual of the Swedish Institutes at Athens and Rome, 2016)
The practice of digging, using, and filling large pits, cut into the ground and sometimes lined with clay, was extensive from the Early Helladic III to the Middle Helladic Period I (c. 2,200–1,900 BC) in large parts of the Aegean area. This particular type of feature is called bothros and has been reported since the early 20th century from many settlements, mainly from the Greek mainland. Although the bothroi are numerous in the archaeological record, few studies of them have been made. During the excavations at Asine, a prehistoric coastal settlement in the Argolid, a number of bothroi were identified. This paper is a contribution to the study of bothroi, and in particular of the faunal remains found within these features. I propose that the bothros was an important part of the domestic organization at Asine. Not only did it reflect spatial boundaries but it was also vital in the construction of “home”. This is based on the zooarchaeological analysis and subsequent statistical processing of the faunal remains recovered from the features. New radiocarbon dates are presented which are used in establishing a chronology of the bothroi at Asine.